SARS-CoV-2 infectivity can be modulated through bacterial grooming of the glycocalyx - Martino, Cameron; Kellman, Benjamin P.; Sandoval, Daniel R.; Clausen, Thomas Mandel; Cooper, Robert; Benjdia, Alhosna; Soualmia, Feryel; Clark, Alex E.; Garretson, Aaron F.; Marotz, Clarisse A.; Song, Se Jin; Wandro, Stephen; et al. (American Society for Microbiology, 2025)
The gastrointestinal (GI) tract is a site of replication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and GI symptoms are often reported by patients. SARS-CoV-2 cell entry depends upon heparan sulfate (HS) proteoglycans, which commensal bacteria that bathe the human mucosa are known to modify. To explore human gut HS-modifying bacterial abundances and how their presence may impact SARS-CoV-2 infection, we developed a task-based analysis of proteoglycan degradation on large-scale shotgun metagenomic data. We observed that gut bacteria with high predicted catabolic capacity for HS differ by age and sex, factors associated with coronavirus disease 2019 (COVID-19) severity, and directly by disease severity during/after infection, but do not vary between subjects with COVID-19 comorbidities or by diet. Gut commensal bacterial HS-modifying enzymes reduce spike protein binding and infection of authentic SARS-CoV-2, suggesting that bacterial grooming of the GI mucosa may impact viral susceptibility.